Comparative Study Of The Shear Strength Between Resin Cement And Y-TZP Zirconia treated With aluminum oxide granules and carbide burs - صقر, ريما; حيدره محمد بدور (Latakia University Journal -Medical Sciences Series, 2024)
Statement of problem:The use of zirconia in dentistry dates back to the early 1990s.Yttria-stabilized tetragonal polycrystal zirconia (Y-TZP) is one of the most common types of zirconia used in fixed prostheses, due to its high mechanical properties. This ceramic is crystalline and cannot be etched chemically, as glass-ceramics do. As a result, mechanical etching was used more heavily to ensure appropriate surface roughness, increase microscopic depressions, and allow the resin cement to hydrate and flow, so that this bond will be stronger and these prostheses will be more stable, especially when the abutments are short or over-prepared. By either sandplasting with aluminum oxide granules or roughening with burs, this can be accomplished. Aim of the study: The purpose of this study was to compare the shear strength between resin cement and zirconia treated with mechanical etching with aluminum oxide granules and carbide burs, in order to evaluate the best bond strength between them. Materials and methods: CAD/CAM was used to mill 20 zirconia discs for the research sample. The sample was divided into two groups based on the zirconia surface treatment: the sandblasting group with aluminum oxide granules included 10 discs. The etching (roughening) group with tungsten carbide burs included 10 discs. They were cemented to the buccal surfaces of healthy upper premolars prepared with a specific area and thickness, using Adhesive Resin Cement. At 37°, they were kept in water for 24 hours. A universal mechanical test machine was used to conduct the shear strength test, and the results were recorded. Results: According to T student test of independent samples at a 95% confidence level, there were no statistically significant differences between the two groups (the sandblasting group with aluminum oxide granules - the roughing group with carbide burs) in the average values of shear strength. Conclusions: Based on the findings of this study, we conclude: The carbide burs used in treating zirconia surfaces provided a shear strength, as did sandblasting with aluminum oxide granules, and both methods provided a comparable bond strength with resin cement.